The involvement of the phenylpropanoid and jasmonate pathways in methyl jasmonate-induced soft rot resistance in kiwifruit (Actinidia chinensis) - Li, Shucheng; Xiao, Liuhua; Chen, Ming; Cao, Qing; Luo, Zhenyu; Kang, Naihui; Jia, Mingshu; Chen, Jinyin; Xiang, Miaolian (Frontiers in Plant Science, 2022)
Botryosphaeria dothidea is a major postharvest causal agent of soft rot in kiwifruit. Methyl jasmonate (MeJA) is an important plant hormone that participates as a plant defense against pathogens from a signal molecule. However, the impact and regulatory mechanism of MeJA on the attenuation of kiwifruit fungal decay remains unknown. This work investigated the effects of exogenous MeJA on the enzyme activity, metabolite content and gene expression of the phenylpropane and jasmonate pathways in kiwifruit. The results revealed that MeJA inhibited the expansion of B. dothidea lesion diameter in kiwifruit (Actinidia chinensis cv. ‘Hongyang’), enhanced the activity of enzymes (phenylalanine ammonia lyase, cinnamate 4-hydroxylase, 4-coumarate: coenzyme A ligase, cinnamyl alcohol dehydrogenase, peroxidase and polyphenol oxidase), and upregulated the expression of related genes (AcPAL, AcC4H, Ac4CL, and AcCAD). The accumulation of metabolites (total phenolics, flavonoids, chlorogenic acid, caffeic acid and lignin) with inhibitory effects on pathogens was promoted. Moreover, MeJA enhanced the expression of AcLOX, AcAOS, AcAOC, AcOPR3, AcJAR1, AcCOI1 and AcMYC2 and reduced the expression of AcJAZ. These results suggest that MeJA could display a better performance in enhancing the resistance of disease in kiwifruit by regulating the phenylpropanoid pathway and jasmonate pathway.